Las mujeres del teatro de Miguel Hernández: construcción dramatúrgica del personaje (Estudios Humanísticos. Filología, 1996)
This paper pays attention to an aspect in the drama of Miguel Hernández that has so far not been the subject of much analysis. Here the dramaturgical analysis of his female characters is made bearing in mind the world view of the poetplaywright in two aspects: one based on his personal experience, and the other deriving from the literary tradition he assimilated. This double vision leads him to the building of a feminine typology of archetypal behaviours determined by a canonically patriarchal world view, and qualified by the characters of the literary heroines stemming from the playwright's reading. The result is the fiancées/wives, sisters an mothers, women defending the honour that would be taken from them by force, or beloved women whose resistance makes their ardent lovers suffer. However, in En Labrador de más aire there is a feminine character that is spontaneous and authentic in her emotions, and whom the author hes endowed with an outspoken vehement nature.